Data Sheet 7_LL37-driven mast cell degranulation and inflammation in rosacea via TLR2/JAK2/STAT3 axis.zip - Huiping Fan (13921872) (2025)
Introduction Rosacea is a chronic inflammatory facial dermatosis with incompletely elucidated pathogenesis. LL37 is a key molecular mediator in rosacea development, and mast cells represent pivotal immune players in this process. However, the precise mechanism underlying LL37-induced mast cell degranulation remains undefined. Methods A LL37-induced rosacea-like dermatitis mouse model was established with or without ruxolitinib treatment. Hematoxylin-eosin and toluidine blue staining were used to evaluate the pathological changes. Mice skin lesions were collected for transcriptome sequencing, Western blot and immunofluorescence. In vitro, the interaction between LL37 and TLR2 on the mast cell membrane surface was detected by co-immunoprecipitation and fluorescence staining. The activation of the TLR2/MyD88/JAK2/STAT3 signaling pathway was investigated using lentivirus-mediated TLR2 knockdown, MyD88 overexpression, combined with JAK2 inhibitor (ruxolitinib). Ten patients underwent VISIA skin analysis system and severity assessment following topical ruxolitinib treatment. Results LL37 induces activation of the TLR2/JAK2 pathway in mast cells of rosacea-like mice. Ruxolitinib ameliorated cutaneous erythema and reduced mast cell infiltration and degranulation. In vitro experiments demonstrated that LL37 directly binds to TLR2, triggering TLR2/MyD88 pathway activation and subsequent mast cell degranulation. Mechanistically, MyD88 directly interacts with JAK2 to modulate the JAK2/STAT3 signaling axis, which governs mast cell degranulation. Topical application of ruxolitinib exhibited clinical efficacy in rosacea patients. Conclusion These findings collectively demonstrate that LL37 drives mast cell activation and degranulation in rosacea pathogenesis via TLR2/JAK2/STAT3 pathway activation, while ruxolitinib effectively suppresses this signaling axis. This study provides novel mechanistic insights and therapeutic strategies for rosacea management.